Improving Effectiveness in Fundraising for Non-Profit Organization. Study Case: Indonesia Mengajar - Almanda, Raissa Listy; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2015)
Abstract.Indonesia Mengajar is a non-profit organization focusing in education movement. Indonesia Mengajar believes that it is every citizen’s duty to fulfill the constitution promises to educate the nation. Indonesia Mengajar main program is assigning young teacher to serve as a teacher for a year in rural areas of Indonesia. Along with young teacher program, Indonesia Mengajar also initiates various education movements involving volunteers from all over Indonesia.The corporation sector has supported the funds since the organization first established and still become the largest contributors in supporting the organization’s operational expenses. However, the development of Indonesia Mengajar had encourages many audiences to contribute in education movement. To accommodate these audiences, Indonesia Mengajar launch a new funding scheme for institution and public donors in 2014.Research was conducted through internal organization, public individual, institution, and corporation to gain perspective from various audiences about involvement and support in education movement and Indonesia Mengajar. The collected data were analyzed using SWOT and PESTEL to get current situation analysis.Managing non-profit organization is quite similar with for-profit organization. The difference only occurs in the differentiation between maximizing profit in for-profit organization and leveraging social impact in non-profit organization. Thus, implementation business strategy can also be applied in non-profit organization with certain adjustment. The author recommends adapting New Wave Marketing as a strategy to engage the donors. The implementation of 12Cs in New Wave Marketing theory would be a consistent approach for Indonesia Mengajar to improve the effectiveness in fundraising through involvement and social networking.Keywords: non-profit organization, education, movements, volunteers, donation, involvement, fundraising, business strategy, marketing strategy, social responsibility, community development.